Masticatory function in complete denture wearers varying degree of mandibular bone resorption and occlusion concept: canine-guided occlusion versus bilateral balanced occlusion in a cross-over trial - Pero, Ana Carolina [UNESP]; Scavassin, Priscila M. [UNESP]; Policastro, Vivian B. [UNESP]; de Oliveira Júnior, Norberto M. [UNESP]; Mendoza Marin, Danny Omar [UNESP]; Silva, Marcela Dantas Dias da [UNESP]; Cassiano, Ana Flávia B. [UNESP]; Santana, Thais de Sousa [UNESP]; Compagnoni, Marco Antonio [UNESP] (Japan Prosthodontic Society, 2019)
Purpose: The present cross-over study evaluated the masticatory function and maximum occlusal force of edentulous patients with complete dentures with bilateral balanced occlusion (BBO) and canine guidance (CG), with normal (NR) and resorbed mandibular ridges (RR). Methods: Participants received new complete dentures and both occlusal concepts (BBO and CG) were applied for a period of 30 days each. The masticatory performance was evaluated with the sieving method; masticatory ability with a visual analog scale (VAS) and maximum occlusal force was assessed by means of a gnatodynamometer. Data were analyzed using repeated-measure ANOVA or Generalized Estimating Equations (GEEs), α = 0.05. Results: Thirty women completed the trial. The height of mandibular ridge was significant for the masticatory performance (ANOVA, p < 0.001, NR = 46.35 ± 12.18%, RR = 30.39 ± 9.94%), regardless of the occlusion guidance. A significant effect of the occlusion guidance was observed for the maximum occlusal force (ANOVA, p = 0.021, CG = 31.99 ± 12.74 N, BBO = 28.37 ± 9.83 N). The occlusion guidance was not significant for the masticatory performance (ANOVA, p = 0.156) and the height of the mandibular ridge did not influence on the occlusal force (ANOVA, p = 0.060). The interaction of the factors (guidance × ridge) was not significant for masticatory performance (ANOVA, p = 0.184) and occlusal force (ANOVA, p = 0.236). The VAS scores showed a significant effect of the ridge on chewing of lettuce, resulting in greater ease (GEEs, p = 0.016) and chewing quality (GEE, p = 0.028) of this food for participants with resorbed ridges. Participants with CG reported greater ease of chewing fresh bread and beef, and expressed higher quality of chew raw carrot. Participants with CG and normal ridges exhibited the highest overall chewing ability, in comparison to BBO (Bonferroni, p < 0.05, CG = 91.9, BBO = 72.7). Conclusions: CG represents a viable alternative to the BBO in complete dentures with satisfactory clinical results related to the self-perception of chewing and occlusal force.
Keywords: Bite force; Complete denture; Dental occlusion balanced; Mastication; Randomized controlled trial